2009
DOI: 10.1002/jcp.21781
|View full text |Cite
|
Sign up to set email alerts
|

Acrosomal exocytosis of mouse sperm progresses in a consistent direction in response to zona pellucida

Abstract: Sperm acrosomal exocytosis is essential for successful fertilization, and the zona pellucida (ZP) has been classically considered as the primary initiator in vivo. At present, following what is referred to as primary binding of the sperm to the ZP, the acrosome reaction paradigm posits that the outer acrosomal membrane and plasma membrane fuse at random points, releasing the contents of the acrosome. It is then assumed that the inner acrosomal membrane mediates secondary binding of the sperm to the ZP. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 45 publications
(49 reference statements)
4
33
0
Order By: Relevance
“…Another report by Buffone et al (2009b) using acrosin-GFP transgenic mice showed the differences of the rate and region of intra-acrosomal GFP signals loss during the acrosome reaction after comparison with those induced by solubilized zona pellucida proteins …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another report by Buffone et al (2009b) using acrosin-GFP transgenic mice showed the differences of the rate and region of intra-acrosomal GFP signals loss during the acrosome reaction after comparison with those induced by solubilized zona pellucida proteins …”
Section: Discussionmentioning
confidence: 99%
“…under spontaneous acrosome reaction) and since the progression speed of the acrosome reaction was slower than that of artificial acrosome reaction. In addition, Buffone et al (2009b) proposed that the acrosome reaction orderly occurs with membrane fusion between plasma membrane and OAM under the controlled receptor-mediated manner, forming hybrid vesicles and releasing acrosomal components. In this context, the present model of the acrosome reaction progression based on the equatorin behavior will be useful to further analyze the molecular mechanism during the acrosome reaction.…”
Section: (A-c) Initial Stage (Initial) (D-f) Early Stage (Early) (Gmentioning
confidence: 99%
See 1 more Smart Citation
“…The now exposed intra-acrosomal layer of proteins consists of an array of proteins that interact with the zona pellucida (for review see [7]). This so-called secondary zona binding was thought to be specific to ZP2 [66][67][68] but recently it has been shown that the intra-acrosomal protein sp56 binds to ZP3 [4,12].…”
Section: Zona Penetration After the Acrosome Reactionmentioning
confidence: 99%
“…The membrane fusions are induced when the sperm cell binds to specific zona binding proteins at the sperm surface [3][4][5][6][7]. The acrosome exocytosis is a multipoint membrane fusion event between the sperm plasma membrane and the outer acrosomal membrane (see Fig.…”
Section: Introductionmentioning
confidence: 99%